Grenada : Poverty Reduction Strategy Paper-Preparation Status Report. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2008)
The Poverty Reduction Strategy Papers (PRSPs) of Grenada outline the issues raised in the Joint Staff Assessment. In the area of poverty diagnostics, a more detailed discussion of poverty based on updated poverty data is provided. The PRSP will describe the links between poverty, growth, and unemployment and the economic growth required to advance the social agenda. In the area of costing of initiatives, the full costs of social policies and programs, their relationship to the budgetary envelope, and identity of associated recurrent costs will be evaluated.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet
Keywords: CR; ISCR; Policy; Poverty Diagnostic; Priority; Grenada